Cegah Stroke dengan Pola Hidup Sehat di Puskesmas Kroya - Khamdiyah Indah Kurniasih; Esanda Falentine Milani; Fadilla Nur Salsabila; Fitria Putri Ari Susanti; Hafiz Ganindya T. H.; Heni Yuliana Dewi (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Stroke is one of the leading causes of death and disability worldwide, most of which can be prevented through control of modifiable risk factors. Risk factors such as hypertension, diabetes mellitus, dyslipidemia, obesity, smoking, lack of physical activity, and unhealthy diets contribute to the increasing incidence of stroke. This health promotion activity aims to increase participants’ knowledge about risk factors and stroke prevention through the implementation of a healthy lifestyle. The activity was carried out at the Kroya I Community Health Center, Cilacap Regency, on May 22, 2026, involving 30 participants of the Chronic Disease Management Program (Prolanis). The methods used were interactive lectures, discussions, and evaluations through pre-tests and post-tests, each consisting of 10 questions, which were then analyzed using a Paired Sample T-Test. There was an increase in the level of knowledge of participants, indicated by an increase in the average pre-test score from 68.00 to 95.00 in the post-test. The results of the Paired Sample T-Test showed a significance value of <0.001, indicating a significant effect of education on increasing participants’ knowledge. Thus, health education through interactive lecture methods is effective in increasing participants’ knowledge and awareness regarding stroke prevention through the implementation of a healthy lifestyle.